Investigation of Teacher Candidates' Digital Well-Being Levels with Respect to Various Variables - Karabatak, Songul; Polat, Ebru; Alanoglu, Muslim (Institute of Electrical and Electronics Engineers Inc., 2024)
This study aims to investigate the levels of teacher candidates' digital well-being concerning various variables. The research employed a survey model, which is a quantitative research method. The participants in the study were 309 teacher candidates enrolled at a university in eastern Turkey. The study utilized a Personal Information Form and the Digital Well-being Scale. The study's findings indicate that the participants' overall digital well-being, digital satisfaction, and digital wellness scores were high, while their safe and responsible behavior scores were moderate. Gender did not emerge as a significant factor in the digital satisfaction and safe and responsible behavior sub-dimensions, but it showed a significant difference in favor of female teacher candidates in the digital wellness sub-dimension. Moreover, the digital satisfaction sub-dimension showed a notable difference in favor of teacher candidates who reported Internet usage of more than 5 hours and 3-5 hours. The general Digital Well-Being Scale and its sub-dimensions demonstrated a significant difference in favor of participants who reported updating their mobile device security tools several times a month. © 2024 IEEE.
12th International Symposium on Digital Forensics and Security, ISDFS 2024 -- 29 April 2024 through 30 April 2024 -- San Antonio -- 199532
Keywords: digital well-being; teacher candidates; well-being